Exploring the lived experiences of women with breast cancer: Navigating stigma and social distancing in their social and family networks - Abu-abbas, Manar; Abudari, Mohammad Othman; Alrida, Nour Ali Assaf; Al-Shatnawi, Feda; Khatatbeh, Haitham; Abu-Shaikha, Ma'in (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the lived experiences of Jordanian women diagnosed with breast cancer, with particular attention to the ways stigma and social distancing shape relationships within family and social networks. Breast cancer is the most prevalent malignancy among women in Jordan, and the meanings attached to the disease are deeply entangled with cultural expectations of femininity, family honor, and religious belief. Drawing on a phenomenological approach, the research explores how women interpret and respond to stigma, how family members provide or withhold support, and how social norms affect disclosure and interaction. The findings, drawn from qualitative interviews, suggest that stigma is both externally imposed and internally anticipated, leading women to negotiate between seeking support and protecting family reputation. While female relatives often emerge as crucial sources of emotional and practical assistance, experiences of concealment, fear of marital breakdown, and reduced social engagement remain widespread. The study highlights the need for culturally grounded psychosocial interventions, improved communication between healthcare providers and patients, and public health campaigns that address stigma directly. By situating women’s narratives within the Jordanian sociocultural context, the research contributes to a deeper understanding of the intersection between illness, gender, and social belonging in the region.